Validation of a Cellular Imaging‐Based Method as a Potential Biomarker for SPG4 Hereditary Spastic Paraplegia - Gaia Fattorini; Valerio Licursi; Gianmarco Dalla Zanna; Flavio Dal Canto; Melissa Barghigiani; Nunzio Setola; Salvatore Rossi; Antonio Funcis; Filippo M. Santorelli; Gabriella Silvestri; Carlo Casali; Francesca Sardina; et al. (Annals of Clinical and Translational Neurology, 2026)
ABSTRACT Background Hereditary Spastic Paraplegia (HSP) comprises a group of rare genetic diseases characterized by length‐dependent axonal degeneration of the corticospinal tracts and dorsal columns, whose main clinical feature is spastic gait. Pathogenic variants in the SPG4 gene cause Spastic Paraplegia Type 4 (SPG4‐HSP), the most common form of HSP. SPG4/SPAST encodes spastin, a protein involved in microtubule regulation and lipid droplet behavior. SPG4‐HSP shows extreme heterogeneity in both clinical manifestations and genetics. Although no cure is currently available, several strategies aimed at restoring spastin levels are emerging; however, SPG4‐HSP still lacks accessible cellular readouts for clinical studies. This study evaluates a cell‐imaging approach that quantifies the distance between nucleus and cell centroid (dcnc) in peripheral blood mononuclear cells (PBMCs) in a genetically and clinically heterogeneous SPG4‐HSP cohort. Methods PBMCs from 48 molecularly confirmed SPG4‐HSP patients and 21 healthy controls (HC) were analyzed by automated cell imaging. Dcnc and additional cytoskeletal and lipid droplet‐related parameters were measured. Patient‐level discrimination was assessed via cross‐validated classification; correlations with molecular and clinical features were explored. Results At the patient level, dcnc distinguishes SPG4‐HSP from HC, independently of mutation type and disease severity, supporting robust cross‐validated classification and inverse correlation with spastin protein levels. Conclusion Dcnc is a robust, non‐invasive, and mutation‐independent cellular candidate biomarker for SPG4‐HSP. It also offers preliminary evidence consistent with spastin target engagement supporting evaluation in future clinical trials.